The energy spectrum of cosmic rays at the highest energies - Tsunesada Yoshiki; Pravdin Mikhail I.; Ikeda Daisuke; Ivanov Dmitri; Abu-Zayyad Tareq; Salamida Francesco; Roth Markus; Mariş Ioana C.; Dawson Bruce R.; Sabourov Artem V. (EPJ Web of Conferences, 2013)
One of several working groups established for this workshop was charged with examining results and methods associated with the UHECR energy spectrum. We summarize the results of our discussions, which include a better understanding of the analysis choices made by groups and their motivation. We find that the energy spectra determined by the larger experiments are consistent in normalization and shape after energy scaling factors are applied. Those scaling factors are within systematic uncertainties in the energy scale, and we discuss future work aimed at reducing these systematics.